(untitled) (Experimental biology, 2016)
By method of optical-emissive spectrometry with inductive-connected argonplasma 15 elements in Lagochilus inebrians and 13 elements in Lagochilus setulosus are revealed. In plant Lagochilus inebrians are found out Se and Ag which were are absent at plant Lagochilus setulosus. But the quantitative content of iron, magnesium, lithium, aluminium in 2-3 times is more at plant Lagochilus setulosus. While the content of potassium, calcium, zinc surpasses at plant Lagochilus Inebrians. At both plants from chemical elements calcium is most of all presented, and the plasma hemostasis in combination with Lagochilin and calcium is realized.